Problems of Teaching ESP at the Technical Universities of Uzbekistan (Eurasian Research Bulletin, 2022)
In this article, the problems of teaching English for special purposes are considered. According to the authors the current problems in teaching ESP have been existed for a long time not only in Uzbekistan but in the other countries as well. The author highlights the key tendencies and problems in this sphere.